Past and present (and future) of parallel and distributed computation in (constraint) logic programming. Issue 5 (5th September 2018) - FIORETTO, FERDINANDO; PONTELLI, ENRICO
Abstract : Declarative languages offer unprecedented opportunities for the use of parallelism to speed up execution. A declarative language, being not procedural, removes the need to perform operations in a strict order and reduces the number of dependencies among operations, thus opening the doors for concurrent execution. The potential for transparent exploitation of parallelism in logic programming emerged almost immediately with the birth of the paradigm (Pollard 1981).